Clinical application of molecular testing for the diagnosis of primary myelofi brosis clinicopathologically mimicking chronic myelogenous leukemia: a case report - Rattarittamrong, Ekarat; Tongphung, Ratchanu; Tantiworawit, Adisak; Chai-Adisaksopha, Chatree; Hantrakool, Sasinee; Norrasetthada, Lalita; Lekawanvijit, Suree (Biomedical Sciences and Clinical Medicine, 2015)
Background Chronic myelogenous leukemia (CML) and primary myelofi brosis (PMF) are both myeloproliferative neoplasms that have overlapped clinical manifestations, but their prognosis and treatment are different. Besides conventional chromosome analysis, molecular testing is required for the correct diagnosis in some patients. Objective To present a case report that applied molecular techniques to diagnose PMF in a patient with CML-like presentation. Results The patient was a 66 year-old male who presented with splenomegaly and marked leukocytosis with left shift. CML was suspected, but chromosome analysis did not demonstrate a Philadelphia chromosome. Reverse transcription- polymerase chain reaction (RT-PCR) and real-time quantitative PCR (RQ-PCR) also were negative for the identifi cation of BCR-ABL1. Analysis of positive JAK2 V617F mutations as well as increased reticulin fi bers in a bone marrow biopsy supported the diagnosis of PMF. Conclusion Molecular diagnostic techniques are required for the diagnosis of MPNs, especially in patients with overlapping clinical manifestations of CML and PMF.